2000
DOI: 10.1007/s11746-000-0141-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of rice protein isolates

Abstract: Various enzymes were used to treat a protein-enriched rice flour for the production of rice protein isolates. The rice flour containing 49% protein was a by-product from the processing of brown rice for syrup production. The treatment sequence of α-amylase followed by glucoamylase was most effective, resulting in a product with 85% protein content. The product was then treated with a mixture of cellulase and xylanase, which raised the protein content in the insoluble fraction to 91%. Inorganic impurities, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
1
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 12 publications
1
63
1
6
Order By: Relevance
“…After removing the hydrolyzed starch as syrup, the insoluble residue contains up to 50% protein and is a low-cost industrial co-product [30,33]. Shih and Daigle [34] reported that treatment of this co-product with a-amylase and glucoamylase resulted in a product containing 85% protein. Follow-up treatment with a mixture of cellulase and xylanase raised the protein content to 92%.…”
Section: Enzymatic Methodsmentioning
confidence: 99%
“…After removing the hydrolyzed starch as syrup, the insoluble residue contains up to 50% protein and is a low-cost industrial co-product [30,33]. Shih and Daigle [34] reported that treatment of this co-product with a-amylase and glucoamylase resulted in a product containing 85% protein. Follow-up treatment with a mixture of cellulase and xylanase raised the protein content to 92%.…”
Section: Enzymatic Methodsmentioning
confidence: 99%
“…This large amount of rice production has led to accumulation of rice byproducts. One of the major by-products is rice bran which is accounted for 8 % of milled rice (Shih and Daigle 2000). Rice bran is a source of proteins, oil,…”
Section: Introductionmentioning
confidence: 99%
“…Diversas enzimas têm sido utilizadas, entre estas, encontram-se a pancreatina, as proteases alcalinas, fúngicas ou bacterianas, em conjunto ou não com a ação de amilases e carboidrases ( AGBOOLA; NG; MILLS, 2005; ANSHARULLAH; CHESTERMAN, 1997;EUBER;PUSKI;HARTMAN JR., 1991;FISCHER et al, 2001;SHAW;SHEU, 1992;SHIH et al, 1999;DAIGLE, 1997;DAIGLE, 2000;TANG;SHELLHAMMER, 2002;WANG et al, 1999).…”
Section: Introductionunclassified
“…Grande parte do arroz polido é consumida diretamente após cozido, mas uma parte significativamente crescente tem sido usada industrialmente na produção de farinha de arroz que é, posteriormente, utilizada como aditivo em gel, pudins, sorvetes e outros produtos similares devido às suas propriedades nutricionais, sua hipoalergenicidade, por possuir sabor agradável e por não interferir na cor do produto final (BRASIL, 1978;CHRASTIL, 1992;JU;RATH, 2001;DAIGLE, 2000).…”
unclassified
See 1 more Smart Citation